ASSESSING RELATIONSHIP BETWEEN BMI AND VITAMIN D IN COVID-19 SURVIVORS - Najmutdinova D.K.; Kalandarova G.B. (Лучшие интеллектуальные исследования, 2024)
Annotation: This study investigates the impact of age, BMI, and vitamin D levels on the severity of COVID-19 in a cohort of 32 patients. It utilizes logistic regression analysis and correlation testing to examine the relationships between these variables and COVID-19 severity, shedding light on potential risk factors and clinical implications.